Establishing Practice Risk Management and Outcomes Claims for Medical Marijuana Dispensaries: Questions Legislators Should Ask - Paul Langley (University of Minnesota Libraries Publishing, 2019)
In a previous commentary in INNOVATIONS in Pharmacy, the case was made that a major oversight in approving the establishment of medical marijuana programs through commercially and not-for-profit operated dispensaries is the failure to put in place standards for the monitoring and reporting of outcomes. It was pointed out that the evidence base is limited for the range of dosing options, administrative routes and conditions treated. The concern is that the ease that patients have in obtaining medical marijuana certification in many states means that a medical marijuana program is, in effect, little different from a recreational program. Dispensaries understandably focus on sales and returns to investors with scant attention given to tracking and reporting outcomes across the range of conditions and symptoms presented.  While this no doubt appeals to investors in reducing administration costs, it makes it virtually impossible to deliver the appropriate and coordinated level of care that patients should expect if a medical marijuana dispensary is to meet it responsibilities in its duty of care. This places dispensaries at malpractice risk. Given this, this commentary focuses on the questions that legislators should ask in licensing medical marijuana dispensaries to ensure they meet a defensible duty of care to their patients.   Article Type: Commentary